Reactions of P-Substituted Phenols with Nitrous Acid in Aqueous Solution - Lissi-Gervaso, E; Rubio-Campos, M (2014)
The reaction of phenols with nitrite (nitrous acid HONO, or its conjugated base, NO2 -) is of importance in stomach fluids (low pH) and in atmospheric hydrometeors (mild acid and basic pH). The initial reaction associated with the oxidation/nitration of 4-substitued phenols promoted by HONO/NO2 depends on the pH of the solution. At low pH, the initial step involves the reaction between HONO and phenol, whereas at basic conditions this involves an electron transfer from the phenoxy anion to nitrogen dioxide (NO2) producing the nitrite anion. The rate of both processes is determined by the donor capacity of the substituent at the 4-position of the phenol, and the data obtained at pH 2.3 follow a linear Hammett-type correlation with a slope equal to -1.23. The partition of the gaseous intermediates (NO and NO2) makes the rate of HONO-mediated oxidation dependent on their gas-liquid distribution. At low pH, the main process is phenol oxidation, even in oxygen-free conditions, and the presence of any 4-substituted phenol decreases the rate of HONO auto-oxidation. © 2013 Wiley Periodicals, Inc.